Pengaruh Pemberian Ekstrak Etanol Daun Etlingera comosa terhadap penurunan kadar glukosa darah dan gambaran histopatologi pankreas tikus putih jantan - Faikah Dyah Utami; Nur Ramadhani; Ayu Wulandari; Syafika Alaydrus; Resa Aprilia Herlin Molano (Journal of Pharmaceutical and Sciences, 2026)
Etlingera comosa is a unique and newly discovered endemic plant species from Central Sulawesi, Indonesia, specifically originating from Tentena. Plants belonging to the Etlingera genus have been reported to possess considerable potential as natural antioxidants. This study aimed to evaluate the effect of the ethanol extract of E. comosa on blood glucose reduction and pancreatic histopathological changes in male white rats. A completely randomized design with a one-way treatment pattern was employed. Thirty male white rats (Rattus norvegicus) were randomly divided into six groups (n = 5 per group): normal control, positive control, negative control, and treatment groups receiving E. comosa ethanol extract at doses of 100, 200, and 400 mg/kg body weight (BW). All groups, except the normal control, were induced with streptozotocin. Blood glucose levels were measured using a glucometer, while pancreatic histopathological damage was evaluated using hematoxylin and eosin (H&E) staining. The results demonstrated significant differences in blood glucose levels throughout the treatment period, as well as significant differences in pancreatic histopathological damage scores among the experimental groups. Administration of the ethanol extract at a dose of 400 mg/kg BW produced a hypoglycemic effect that was not significantly different from the positive control (p > 0.05) but was significantly different from the negative control (p < 0.05). Similarly, the pancreatic damage score in the 400 mg/kg BW group was comparable to the positive control and significantly improved compared with the negative control. These findings indicate that the ethanol extract of E. comosa effectively reduces blood glucose levels and ameliorates pancreatic histopathological damage in streptozotocin-induced diabetic rats, with the most effective dose being 400 mg/kg BW.